2013
DOI: 10.21909/sp.2013.02.631
|View full text |Cite
|
Sign up to set email alerts
|

Men and Women at Work: The Effects of Objectification on Competence, Pay, and Fit for the Job

Abstract: This is an author version of the contribution published on:Questa è la versione dell'autore dell'opera: Men and women at work: The effects of objectification on competence, pay, and fit for the job STUDIA PSYCHOLOGICA, 55 (2), 2013, pp. 139-152 The definitive version is available at: Finally, objectification increases the suitability for low-status jobs, and this is particularly true for women holding service-oriented professions. Implications are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…The higher satisfaction in women could be related to traditional gender roles and cultural stereotypes. Indeed, on the one hand, cultural stereotypes depicting women as relationship and nurturing-oriented and men as taskoriented influence both genders expectations about job (Eagly & Karau, 2002;Okimoto & Heilman, 2012;Rollero & Tartaglia, 2013): in respect to men, women might have lower expectations about their professional aspirations and thus might feel more satisfied than men, professional status being equal (Heinz et al, 2005). On the other hand, in evaluating job satisfaction individuals could make comparison within their gender group: thus, women could feel comparatively more satisfied than men because they consider the labor market positions of other women, rather than all employees (Magee, 2013;Phelan, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…The higher satisfaction in women could be related to traditional gender roles and cultural stereotypes. Indeed, on the one hand, cultural stereotypes depicting women as relationship and nurturing-oriented and men as taskoriented influence both genders expectations about job (Eagly & Karau, 2002;Okimoto & Heilman, 2012;Rollero & Tartaglia, 2013): in respect to men, women might have lower expectations about their professional aspirations and thus might feel more satisfied than men, professional status being equal (Heinz et al, 2005). On the other hand, in evaluating job satisfaction individuals could make comparison within their gender group: thus, women could feel comparatively more satisfied than men because they consider the labor market positions of other women, rather than all employees (Magee, 2013;Phelan, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Supporting H2, erection salience (regardless of penis size) lowered perceived agency, but not experience of male models. In Experiment 2, we aimed to replicate this finding in a Past research showed that objectification may decrease men's perceived suitability for certain professions (Rollero & Tartaglia, 2013). However, the exact mechanism behind this effect is unclear.…”
Section: Methodsmentioning
confidence: 85%
“…We can interpret this finding thinking that in contemporary western societies the female attractiveness easily implies the sexualisation of women ( Liss, Erchull, & Ramsey, 2011 ; Nowatzki & Morry, 2009 ; Rollero, 2013 ). Indeed, while physical attractiveness has been shown to generate a broadly favorable impression of both men and women, investigations of the traits associated with women’s sexiness suggest a stereotype that is damaging for other aspects: for example, it is poor match for high-status jobs ( Glick, Larsen, Johnson, & Branstiter 2005 ; Rollero & Tartaglia, 2013 ; Tartaglia & Rollero, 2015 ). The job of our targets was salient, as targets of our study were described only in relation to their profession.…”
Section: Discussionmentioning
confidence: 99%
“…During the pretest, participants were also asked to rate a list of 14 jobs on a 5-point scale ranging from 1 (very low status) to 5 (very high status). We chose the jobs that in a previous study on a similar population have been evaluated neither typically masculine nor typically feminine ( Rollero & Tartaglia, 2013 ). We used these evaluations to select the two jobs rated lowest (Call centre operator, M = 1.85) and highest (Doctor, M = 4.50) in status.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation